Perawatan Ortodontik Alat Lepasan Kombinasi Semi-Cekat pada Kehilangan Gigi 46 - Maharetta Ditaprilia; Wayan Ardhana; Christnawati Christnawati (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2015)
Salah satu pertimbangan dalam menentukan alat ortodontik yang akan digunakan adalah biaya. Alat ortodontik lepasan dipilih karena memerlukan biaya yang lebih rendah dibanding dengan alat ortodontik cekat. Perawatan ortodontik dengan alat lepasan sulit dilakukan jika disertai dengan pencabutan satu atau beberapa gigi posterior. Pasien perempuan usia 23 tahun, mengeluhkan gigi rahang atas maju dan gigi rahang bawah berjejal. Pemeriksaan objektif menunjukkan protrusif rahang atas, crowding rahang bawah, palatal bite, disertai kehilangan gigi 46. Maloklusi Angle Kelas II divisi 1 tipe dentoskeletal, hubungan skeletal klas II, protrusif bimaksilar, bidental protrusif, overjet 7,2 mm, crowding, palatal bite, dan kebiasaan bernafas melalui mulut. Perawatan menggunakan kombinasi alat semi-cekat pada rahang bawah dan alat lepasan pada rahang atas. Alat semi-cekat digunakan untuk space clossing bekas pencabutan gigi 46. Terjadi space closing bekas pencabutan gigi 46 setelah 6 bulan perawatan. Overjet berkurang menjadi 4 mm dan overbite 2,7 mm setelah 1 tahun perawatan. Kombinasi alat semi-cekat pada rahang bawah dan alat ortodontik lepasan pada rahang atas efektif untuk koreksi maloklusi Angle Klas II divisi 1 dengan kehilangan gigi 46 pada pasien ini. ABSTRACT: Orthodontic Treatment Using Semi-Fixed Appliances with Partial Edentulous 46. Cost is one of the considerations in determining the use of orthodontic appliances. Removable orthodontic appliance is chosen because it is less costly than fixed orthodontic appliances. It is difficult to use removable orthodontic appliances to treat a missing one or more posterior teeth case. A 23 year old female patient had a chief complaint of crowding in lower anterior teeth and forwardly placed upper anterior teeth. Her objective examination shows protrution of upper teeth, crowding in the lower arch, palatal bite, and partial edentulous of 46 tooth. It was Angle Class II division 1 dentoskeletal malocclusion, skeletal class II, bimaxillary protrusion, bidental protrusion, overjet 7,2 mm, crowding, palatal bite, and mouth-breathing habit. The treatment used a combination of semi-fixed orthodontic appliances in the lower arch and removable appliances in the upper arch. The semi-fixed orthodontic appliances were used on space closing of partial edentulous 46. The partial edentulous 46 was closed after 6 months of treatment. The overjet was reduced to 4 mm and overbite 2,7 mm after one year of treatment. The combination of semi-fixed orthodontic appliances in the lower arch and removable appliances in the upper arch generate a good result to correct Angle Class II division 1 malocclusion with partial edentulous 46.